More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea) - Dworschak, Peter C.; Poore, Gary C. B. (Zootaxa, 2018)
Re-examination of the holotype of Neoaxius nicoyaensis Sakai, 2017 showed that it is conspecific with the axiid Guyanacaris caespitosa Squires, 1979 and thus Neoaxius Sakai, 2017 and Neoaxiidae Sakai, 2017 are respectively subjective junior synonyms of Guyanacaris Sakai, 2011 and Axiidae Huxley, 1879. The types and numerous specimens of the callianassid Trypaea vilavelebita Sakai & Türkay, 2012 are juveniles of the common northeastern Atlantic-Mediterranean species, Callianassa subterranea (Montagu, 1808); the name is therefore a subjective junior synonym. The monotypic callianopsid genera Pleurocalliax Sakai, 2011, Neocallianopsis Sakai, 2011 and Phaetoncalliax Sakai, Türkay, Beuck & Freiwald, 2015 are found not to differ from Callianopsis de Saint Laurent, 1973, the only alleged differences found to be untrue or trivial. Phaetoncalliax mauritana Sakai, Türkay, Beuck & Freiwald, 2015 and Neocallianopsis africana Sakai, Türkay, Beuck & Freiwald, 2015 are thereby transferred to Callianopsis, the latter a subjective junior synonym of the former. Contrary to the assertion of its author, the gourretiid Pseudogourretia portsudanensis Sakai, 2005, the only species in its genus, has no pleurobranchs. The genus Pseudogourretia Sakai, 2005 is therefore synonymised with Gourretia de Saint Laurent, 1973. The respective holotypes of Paracalliax stenophthalmus Sakai, Türkay, Beuck & Freiwald, 2015 and Paracalliax bollorei de Saint Laurent, 1979 were re-examined. Both are from the Banc d’Arguin, off Mauritania, and are identical at the species level. The upogebiid Kuwaitupogebia nithyanandan Sakai, Türkay & Al Aidaroos, 2015 from Kuwait is identical to Upogebia balmaorum Ngoc-Ho, 1990 from the Seychelles, Madagascar and tropical Western Australia. Kuwaitupogebia Sakai, Türkay & Al Aidaroos, 2015 is therefore synonymised with Upogebia Leach, 1814 and Kuwaitupogebiidae Sakai, Türkay & Al Aidaroos, 2015 with Upogebiidae Borradaile, 1903.